Audiovisual Distraction Therapy for Pre School Children with Acute Gastroenteritis and Acute Pain - Nova Ari Pangesti; Eko Riyanti; Ryke Widyasafitri (Institut Citra Internasional, 2026)
One of the diseases in pediatric patients with a fairly high incidence rate globally is gastroenteritis. One of the nursing problems that arise is pain. Pain is based on conditions such as diarrhea that can cause the emergence of pain perception due to the release of histamine that stimulates pain receptors. Untreated pain problems in pediatric patients can trigger other complex problems and can prolong the recovery period. One effective non-pharmacological method for managing pain is audiovisual distraction. The purpose of this study was to determine the results of audiovisual distraction therapy in pediatric patients experiencing acute gastroenteritis with acute pain at Majenang Regional Hospital. This study was conducted using a case study design . Data collection for this study was carried out through interviews, observation, and documentation. The subjects in this study were two children (2-4 years old) who experienced AG with acute pain at Majenang Regional Hospital. The pain measurement tool used was the FLACC scale. Audiovisual distraction given for 10 minutes in children experiencing acute gastroenteritis with acute pain resulted in a decrease in pain levels, although not a significant change, and the patient was calmer. In An. N pain scale 2 (mild) changed to scale 0 (no pain), while in An. R pain scale 6 (moderate) changed to scale 4 (moderate). Audiovisual distraction reduce the scale of acute pain in pediatric patients experiencing acute gastroenteritis. It is hoped that therapy can be applied independently to reduce pain in children with acute gastroenteritis.